Protective effects of black shallot extract against acetaminophen- induced nephrotoxicity in mice - Nhung, Tran Thi Phuong; Quoc, Le Pham Tan (Acta Biologica Szegediensis, 2024)
Acetaminophen (APAP), widely recognized for its analgesic and antipyretic properties, poses a risk of renal toxicity in cases of overdose. Traditional herbal remedies are frequently employed to counteract drug-induced renal damage. This study focuses on black shallot, an innovative food product derived from Allium ascalonicum, a plant highly valued in traditional Vietnamese medicine. The aim is to explore the protective effects of black shallot ethanol extract (BSEE) against APAP-induced nephrotoxicity in mice. BSEE was orally administered at various doses (200, 250, and 300 mg/kg) in combination with APAP (3 g/kg). N-acetylcysteine (NAC) (50 mg/kg) served as the reference drug, while saline (10 mL/kg) functioned as the negative control. Evaluations encompassed renal histology, serum and urine renal function tests, antioxidant enzyme concentrations (SOD, CAT, and GPx), lipid peroxidation, and anti-inflammatory cytokines (TNF-α, IL-1β, and IL-6). The findings indicated significant alterations in total protein, albumin, BUN, and serum/urine CRE concentrations (P < 0.05), coupled with a decrease in malondialdehyde (MDA) levels (P < 0.05) and inflammatory cytokines TNF-α, IL-1β, and IL-6 (P < 0.05). Remarkable elevations were observed in antioxidant enzyme concentrations, including renal catalase (CAT), superoxide dismutase (SOD), and glutathione peroxidase (GPx) (P < 0.05). The macroscopic and microscopic structures of the kidneys exhibited significant improvement. Consequently, BSEE effectively safeguards against APAP-induced renal damage, as evidenced by enhanced renal structure, reduced inflammation, and biochemical modulation, highlighting its potential therapeutic application in preventing APAP-induced nephrotoxicity.